A Qualitative Study of NIMBYism for Waste in Smaller Urban Areas of a Low-Income Country, Mzuzu, Malawi. (January 2021) - Holm, Rochelle H; Chunga, Brighton A; Mallory, Adrian; Hutchings, Paul; Parker, Alison
When waste management infrastructure is built, there can be resistance from the local affected populations, often termed the Not in My Backyard (NIMBY) phenomenon. This study aims to understand the forms of resistance that may develop in such contexts, focusing on 2 solid waste and 1 liquid waste management site within Mzuzu City, Malawi. At the newest solid waste site, community resistance had grown to the extent that the site was reportedly destroyed by the local community. Interviews and observations of the sites are complemented by examining historic and recent satellite images. It was found that, at the new solid waste site, community engagement had not been conducted effectively prior to construction and as part of ongoing site operations. This was compounded by poor site management and the non-delivery of the promised benefits to the community. In contrast, at the liquid waste site, the community could access untreated sludge for use as fertilizer and were happier to live within its vicinity. While NIMBYism is a frustrating phenomenon for city planners, it is understandable that communities want to protect their health and well-being when there is a history of mismanagement of waste sites which is sadly common in low-income settings. It is difficult for government agencies to deliver these services and broader waste management. In this study, an unsuccessful attempt to do something better with a legitimate goal is not necessarily a failure, but part of a natural learning process for getting things right.